Therapeutic drug monitoring vs. pharmacogenetic testing in the context of elevated olanzapine concentrations and prior clozapine intolerability: a case study - Farah Khorassani; Ricardo Azevedo; Reza Farokhpay (BMC Psychiatry)
Abstract Background Strong evidence for therapeutic drug monitoring exists for olanzapine and clozapine, however, olanzapine therapeutic drug monitoring is often underutilized. Evidence for pharmacogenomic-guided dosing of antipsychotics is not as robust, especially for cytochrome P450 1A2 metabolized agents such as olanzapine and clozapine. Herein, we present a case involving a patient suspected of having poor CYP1A2 metabolism. Therapeutic drug monitoring of olanzapine was employed to guide the titration of clozapine following olanzapine failure. Despite pursuing pharmacogenetic testing, no meaningful results were obtained due to the omission of CYP1A2 variants associated with poor metabolism. Case presentation A 32-year-old Caucasian male with schizoaffective disorder-bipolar type, ADHD, and autism spectrum disorder presented with extrapyramidal symptoms due to antipsychotic polypharmacy, resulting in multiple falls. He experienced a partial response to olanzapine 40 mg, thus his dose was increased to 50 mg. Sampling an olanzapine trough revealed a supratherapeutic level of 152 ng/mL. Given his history of EPS and other reported adverse effects from antipsychotics, including clozapine, pharmacogenomic testing was pursued. The patient cross-tapered to clozapine slowly, with the knowledge that the patient would likely exhibit elevated levels of olanzapine. Clozapine was efficacious and tolerated well. As expected, the patient exhibited higher clozapine trough concentrations for someone of his age, ethnicity, and gender. Pharmacogenomic testing yielded no relevant findings relating to olanzapine or clozapine metabolism. Conclusion This case highlights the utility of TDM over pharmacogenetic testing for patients on these medications with a suspected alteration in CYP1A2 metabolism. therapeutic drug monitoring emerges as a more practical approach with stronger evidence for its use, particularly in cases of suspected reduced CYP1A2 activity, where suballeles resulting in decreased enzyme function are not readily detectable on standard commercial pharmacogenomic panels.